Impact of Increasing Levels of Advanced Iterative Reconstruction on Image Quality in Low-Dose Cardiac CT Angiography - Kröpil, P.; Bigdeli, A. H.; Nagel, H. D.; Antoch, G.; Cohnen, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To investigate the effects of an advanced iterative reconstruction (IR) technique on subjective and objective image quality (IQ) in low-dose cardiac CT angiography (CCTA).Materials and Methods: 30 datasets of prospectively triggered “step-and-shoot” CCTA scans acquired on a 256-slice CT scanner with optimized exposure settings were processed on a prototype IR system using filtered back-projection (FBP) and 4 levels of advanced IR (iDose4, Philips) providing incremental rates of IR (level 2, 4, 6, 7). In addition, the effects of different reconstruction kernels (semi-smooth [CB], standard with edge-enhancement [XCB]) and a “multi-resolution” feature [MR] to preserve the noise power spectrum were evaluated resulting in a total of n = 480 image sets. Contrast-to-noise ratios (CNR) were computed from regions of interest at 9 coronary locations. The subjective IQ was rated on a 4-point-scale with “classic” image appearance and noise-related artifacts as main criteria.Results: At an effective dose of 1.7 ± 0.7 mSv, the CNR significantly improved with every increasing level of IR (range: 14.2 – 27.8; p < 0.001) with the best objective IQ at the highest level of IR (level 7). The subjective IQ, however, was rated best at the medium level of IR (level 4) with minimal artifacts and a more “classic” image appearance when compared to higher IR levels. The XCB kernel provided better subjective ratings than CB (p < 0.05) and the MR feature further increased the IQ at a high level of IR.Conclusion: The objective IQ of low-dose CCTA progressively improves with an increasing level of IR. The best subjective IQ, however, is reached at medium levels of IR combined with an edge-enhancing kernel allowing for preservation of a “classic” image appearance suggesting application in the clinical routine.Key Points:• iterative reconstruction (IR) improves image quality in low-dose coronary CTA• objective image quality (CNR) enhances with increasing level of IR• best subjective image quality is reached at medium level of IR• „multi-resolution“ algorithm further improves image quality at a higher level of IRCitation Format:• Kröpil P, Bigdeli AH, Nagel HD et al. Impact of Increasing Levels of Advanced Iterative Reconstruction on Image Quality in Low-Dose Cardiac CT Angiography. Fortschr Röntgenstr 2014; 186: 567 – 575
Keywords: cardiac CT; iterative reconstruction; image quality; CT angiography; dose; iDose